Bridging Sustainable Societies Along Adriatic Peninsulas - Mulita, Reis (Richtmann Publishing, 2012)
The study will introduce a societal model of sustainable development and communication along Adriatic Peninsulas, usingtraditional & modern motorways of seas bridging human values along Adriatic Peninsulas. Historically Adriatic Sea roots have linkedsocieties across Apennines and Balkan Peninsula coasts, bridging diverse social groups, ethnics, cultures, religious, and identities ofEurope and Asia. Under the EU perspectives Adriatic Motorways of the Seas are challenging communication of natural and humanvalues enhancing sustainable developments considering economy, society and environmental impacts. What should do contemporarysocieties along Adriatic coasts to exercise sustainable communication generating long term human wellbeing ? The Present CorridorEight , a Pan European , one â€“ the ancient â€ La Via Egnatia â€œ will be introduced as a case study pointing out societal possibilitiesexercising sustainable developments, linking Apennine with Western Balkans. Literature review, dates analyses, comparisons,interviews, questionnaires using web communications, graphics, etc, will be some methodological approaches finalizing the paperpresentation. Iâ€™ll introduce a new concept of communication bridging Apennines with Western Balkans under sustainable principles of EUexperiences, considering all the Italy as a western gate of Corridor Eight that benefits societies along Adriatic Peninsulas. Cost benefitseconomic activity, law carbon emissions, safe, clean and secure transport for passengers, using motorways of the Adriatic Sea andSeaports of Italy and Albania, should promote touristic activity, using La via Egnatia as a Trace of cultural heritages, archeological sites.Ill conclude the study pointing out that human and natural resources along Adriatic Sea Peninsulas support long term wellbeingâ€™s, whilecontemporary society should use the triangle principles of sustainable development.